Lead the way Reading and writing 6 - Zaki, Zaki Saied; ESC Creative Department ([Cairo] Educational Services Company, 2023)
Lead the Way is a six-level integrated reading and writing series for students ranging from beginners to intermediate.The series is aimed at helping students improve their reading and writing skills through a variety of skill-based activities. Interesting theme- based units are used to motivate students and provide interesting topics for discussions inside the class
English language
Keywords: English language